A MULTI-REGIONS SEIS DISCRETE EPIDEMIC MODEL WITH A TRAVEL-BLOCKING VICINITY OPTIMAL CONTROL APPROACH ON CELLSS. (2017) - CHOUAYAKH, KANZA; RACHIK, MOSTAFA; ZAKARY, OMAR; ELMOUKI, ILIAS
No abstract available